COMPLETELY INVARIANT SUBSPACES OF FREE ALGEBRAS - Najaryan, N.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
A structural theorem is proved for pMqBM completely invariant subspaces of free associative algebras with a unit, having a countable number of free variables over the field of characteristic zero. In particular, it is shown that such spaces contain a Lie nilpotent polynomial.
Keywords: free algebra; T-ideals; linear space; endomorphism; invariant space; module